The framing of anti-fake news law in Malaysian newspapers - Wan, Chen; Waheed, Moniza; Mohd Zawawi, Julia Wirza; Hellmueller, Lea (Human Resource Management Academic Research Society, 2023)
The government of Malaysia enacted an Anti-Fake News law right before the 14th general election. In more ways than one, this law relates to Malaysia’s practice of development journalism, which is a tool for the government to foster economic growth and nation-building. The main aim of this study is to explore the differences between Malaysian serious newspapers and tabloids in terms of frames employed in the Anti-Fake News Law reports. This study applied the generic frames of the framing theory in quantitative content analysis. The serious newspapers chosen in this study were Bernama and The New Straits Times, while the selected tabloids were The Sun and The Malay Mail. Results from the analysis of the 212 news reports retrieved showed that serious newspapers favored the use of the attribution of responsibility frame, while tabloids favored the use of the human interest frame. Additionally, the findings showed that the attribution of responsibility frame was more susceptible to a positive tone and the conflict frame was more susceptible to a negative tone in reports. In conclusion, this study gained insights into journalistic role performance under the practice of development journalism in Malaysia, particularly pertaining to the Anti-Fake News Law.